Reproductive systems and post-pollination barriers between two closely related eu-bromelioids (Bromeliaceae) in the Atlantic Forest of Brazil - Cavalcante, Brayan Paiva; Souza, Everton Hilo De; Williams, Joseph Hill; Versieux, Leonardo M (Botanical journal of the Linnean Society, 2020)
Abstract The eu-bromelioid clade provides a classic example of an exceptionally rapid radiation, in which many closely related species are found in sympatry. In this respect, species cohesion may be due to the rapid evolution of strong reproductive barriers, although interspecific and intergeneric hybridization is observed in the family. The objective of this study was to characterize the breeding systems and post-pollination reproductive barriers in Wittmackia patentissima and Hohenbergia ridleyi. Previously included in Aechmea, they show an almost complete absence of pre-pollination barriers, although their recent divergence may not have allowed time for complete ecological/reproductive isolation to have evolved. In manual pollinations, both species had > 40% fruit set in self and outcross treatments, but seed set from manual self-pollinations was < 50% that of outcrosses, and spontaneous self-pollination produced fewer than three seeds per fruit. Self-pollen and pollen tubes showed no evidence of self-incompatibility, but heterospecific pollen tubes were arrested in the lower part of the style and heterospecific seed set was zero in both species. The combination of self-compatibility and strong post-pollination, pre-fertilization reproductive barriers is consistent with the involvement of breeding system reproductive barriers in allowing closely related bromeliad species to occur in sympatry.